2008
DOI: 10.1080/09513590801921686
|View full text |Cite
|
Sign up to set email alerts
|

beta3-Adrenergic receptor polymorphism and metabolic syndrome in postmenopausal women

Abstract: Trp64Arg polymorphism of the beta(3)-adrenergic receptor gene is not related to metabolic syndrome in postmenopausal Polish women; however, it seems to be associated with decreased HDL-C levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
1
12
1
1
Order By: Relevance
“…In this study, adiponectin concentrations increased markedly in patients who took rosiglitazone for 12 weeks, and a lesser increase of adiponectin was observed in patients with the Trp64Arg genotype, possibly due, in our opinion, to lower PPAR expression in this group. Although without statistical significance, a recent study found the Trp64Arg variant could be associated with lipid profile disorders in postmenopausal women [31]. In our study, the Trp64Arg variant was also associated with a greater decrease of TG and less decrease of LDLcholesterol, but detailed explanation of this phenomenon must await study of larger samples.…”
Section: Discussioncontrasting
confidence: 47%
“…In this study, adiponectin concentrations increased markedly in patients who took rosiglitazone for 12 weeks, and a lesser increase of adiponectin was observed in patients with the Trp64Arg genotype, possibly due, in our opinion, to lower PPAR expression in this group. Although without statistical significance, a recent study found the Trp64Arg variant could be associated with lipid profile disorders in postmenopausal women [31]. In our study, the Trp64Arg variant was also associated with a greater decrease of TG and less decrease of LDLcholesterol, but detailed explanation of this phenomenon must await study of larger samples.…”
Section: Discussioncontrasting
confidence: 47%
“…Involvement of a gene in multiple MetS pathways did not guarantee an association for SNPs in this gene with MetS. The evidence for an association with MetS was weak for SNPs in the ADRB2 (20,21,46,86) and ADRB3 (21,46,87–89) gene, genes involved in glucose metabolism, lipid metabolism and blood pressure regulation (86), SNPs in the LEPR gene (54,90,91), which is involved in body weight regulation, fatty acid oxidation and glucose metabolism (92); SNPs in the PPARD gene (21,93,94), which regulates both glucose and energy metabolism (94); and SNPs in the PPARGC1A gene (11,21,46,95), which is involved in lipid and glucose metabolism (95). However, for the Ala54Thr (rs1799883) SNP (18,35,48,96–98) in the FABP2 gene, which is involved in both fatty acid and glucose metabolism (96,97), some evidence for an association with MetS exists.…”
Section: Resultsmentioning
confidence: 99%
“…10 Simultaneously, lower concentrations of HDL lipoprotein as well as higher concentrations of C-reactive protein are seen in individuals who express the Trp64/Arg64 genotype. 7,11 Individuals with the Trp64Arg genotype are also more likely to develop hyperuricaemia. 12 Similarly, obese individuals who express the Trp64Arg genotype are 2.63 times more likely to develop colon carcinoma in comparison with patients who express the Trp64 genotype.…”
Section: Kathryn Wood and Charles Van Heyningenmentioning
confidence: 99%